Watershed Management Performance Assessment Based on Land Condition Indicators (Laeya Watershed Case, Southeast Sulawesi Province - Sudia, La Baco; Kahirun, Kahirun; Kete, Surya Cipta Ramadhan; Erif, La Ode Muhammad (Universitas Ibn Khaldun Bogor, 2023)
Laeya Watershed is one of the three Priority Watersheds in Southeast Sulawesi. Therefore, monitoring and evaluating watershed performance is very important to ensure that watershed management is sustainable. This study aims to assess the performance of watershed management based on indicators of land conditions in the Laeya Watershed, Southeast Sulawesi Province. The method used is a survey with a scoring technique using the parameters index of the percentage of critical land, vegetation cover, and erosion index to determine the carrying capacity of the watershed. The results showed that the carrying capacity of the Laeya Watershed was classified as very good with a score of 35 (<70), with each sub-criterion of critical land classified as very low with a score of 0.5, sub-criteria for vegetation cover classified as good with a score of 0.75 and sub-criteria the erosion index criteria are classified as very high with a score of 0.75. It can be concluded that the management performance of the Laeya watershed is very good.